Comportamiento silvicultural de semillas de la especie quinilla (manilkara bidentata) en el bosque tropical de Puerto Almendra. San Juan, Maynas, Loreto, 2023 - Paima Saavedra, David (2024)
The present study has been developed in the tropical forest of Puerto Almendra of the Faculty of Forestry Sciences, of the National University of the Peruvian Amazon, with the purpose of knowing the silvicultural behavior of seeds of the quinilla species (Manilkara bidentada) in the tropical forest o f Puerto Almendra, San Juan-Maynas.Loreto 2023, which Will allow us to improve the seed reproduction conditions of the species. From the obtained results, an average weight of 6.1 grams/seed of the species (Manilkara bidentada) – quinilla weighed 5 days after collection was obtained. The purity indexo f the sedes of the species of (Manilkara bidentada) – quinilla was 72.72%. The alternative hypothesis is approved for factor A and for the interaction, however for Factor B the null hypothesis is accepted.